Analisis Kinerja Keuangan Pemerintahan Daerah Berdasarkan Value Money Pada Pemerintah Kota Bandung Tahun 2020-2022 - Satriya Romadhan; Sonny Fransisco Siboro; Shintya Nuraliza Kusuma Putri; Wiwin Veberlina Hia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the financial performance of Bandung Metropolitan City based on the concept of Value for money from 2020 to 2022 by considering economic, efficiency and effectiveness perspectives. The use of this research method is Descriptive Qualitative Analysis Method. The analysis method used includes financial data regarding the city's income, expenditure and investment during this period. This study uses an evaluative approach to assess the efficiency of regional financial management and its impact on the regional economy. The results showed that the financial performance of the Bandung City Government was able to maintain its economic index. In terms of efficiency, the financial performance of Bandung City Government from 2020 to 2022 is less stable. This shows that the Bandung City Government basically needs to minimize the use of resources and again increase efficiency. In terms of effectiveness, it is clear that the Bandung City Government has been able to implement the applicable standards for three years.